The front end in radical process innovation projects: Sources of knowledge problems and coping mechanisms. (July 2021) - Simms, Christopher; Frishammar, Johan; Ford, Nicholas
Abstract: When companies in process industries take radical leaps in product innovation, these new products often fall outside the "process window" of existing production processes and hence require extensive production line modifications and radical process change. Consequently, firms need to deal with high degrees of uncertainty, complexity, equivocality and ambiguity in the front-end. These four knowledge problems constitute important challenges to managers and engineers when a new process definition is created. Prior research into the front end of process innovation is limited, and for radical projects close to non-existent. We analyse six radical process innovation projects situated in the food processing industry in the United Kingdom and provide three key contributions. First, we uncover the underlying sources of knowledge problems, and the specific coping mechanisms used to address them. Second, we offer a framework that delineates the relationships between the sources of knowledge problems, the knowledge problems per se, and the coping mechanisms which enable more effective decision-making regarding the creation of process concepts and definitions. Finally, we extend prior studies of the front end by revealing the challenges faced with respect to ambiguity, thus providing a more granular understanding of fuzziness. Altogether, these findings provide important theoretical and practical implications. Highlights: This paper investigates the front end of radical process innovation. Detailed analysis of the sources of knowledge problems are provided. Coping mechanisms to manage each type of knowledge problem is uncovered. A framework which enables more effective creation of process concepts and definitions is provided.